2020
DOI: 10.1016/j.yebeh.2020.107350
|View full text |Cite
|
Sign up to set email alerts
|

Access to healthcare and prevalence of anxiety and depression in persons with epilepsy during the COVID-19 pandemic: A multicountry online survey

Abstract: Objective The objective of this study was to assess access to healthcare and to estimate the prevalence of depression and anxiety among persons with epilepsy (PWE) during the ongoing coronavirus disease 2019 (COVID-19) pandemic. Methods We conducted a multicountry online survey among PWE. Persons with epilepsy were invited to participate through various social media channels. The Hospital Anxiety and Depression Scale (HADS) and 9-item Patient Health Questionnaire (PHQ-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 41 publications
5
75
5
2
Order By: Relevance
“…Neither our survey nor the other reported surveys were designed to provide information on SARS-CoV-2 infection in PwE, however their collective data seem to indicate prevalence rates reflecting those in the general population (9). A worsening of seizures has been signaled in some cases (12), including one of the two patients who reported the infection in our survey.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Neither our survey nor the other reported surveys were designed to provide information on SARS-CoV-2 infection in PwE, however their collective data seem to indicate prevalence rates reflecting those in the general population (9). A worsening of seizures has been signaled in some cases (12), including one of the two patients who reported the infection in our survey.…”
Section: Discussionmentioning
confidence: 68%
“…In this latter study, female gender and financial problems were significantly associated both with anxiety and with depression. Living in high-income countries decreased the odds for anxiety, while difficulties accessing ASMs increased the odds for depression (12).…”
Section: Depression and Anxietymentioning
confidence: 96%
See 1 more Smart Citation
“…However, due to the lack of uniformity between these studies, we here focus solely on confirmed diagnoses. The rate of confirmed SARS-CoV-2 infections was 0.2-2.5% (3,5,7,9,12), which generally corresponded to the expected background for the given country in the same period. In the study by Assenza et al, the rate of infection in people with and without epilepsy was comparable (0.2 vs. 0.4%) (9).…”
Section: Covid-19 Confirmed Diagnosissupporting
confidence: 52%
“…(10) In a large multinational survey, 22.8% of PwE reported financial problems, including difficulty paying housing costs/bills, eating properly and paying for ASMs. These issues were significantly more common in people living in lowto middle-income countries (12).…”
Section: Lockdown-related Problemsmentioning
confidence: 99%